Ultrafast photoinduced electron transfer in face-to-face charge-transfer π-complexes of planar porphyrins and hexaazatriphenylene derivatives. Issue 2 (15th December 2014) - Aoki, Toru; Sakai, Hayato; Ohkubo, Kei; Sakanoue, Tomo; Takenobu, Taishi; Fukuzumi, Shunichi; Hasobe, Taku
Abstract : We have successfully observed ultrafast photoinduced electron transfer in face-to-face charge-transfer π-complexes of planar porphyrins and hexaazatriphenylene derivatives. Abstract : Charge-transfer (CT) π-complexes are formed between planar porphyrins and 1, 4, 5, 8, 9, 12-hexaazatriphenylene (HAT) derivatives with large formation constants ( e.g., 10 4 M −1 ), exhibiting broad CT absorption bands. The unusually large formation constants result from close face-to-face contact between two planar π-planes of porphyrins and HAT derivatives. The redox potentials of porphyrins and HAT derivatives measured by cyclic voltammetry indicate that porphyrins and HAT derivatives act as electron donors and acceptors, respectively. The formation of 1 : 1 CT complexes between porphyrins and HAT derivatives was examined by UV-vis, fluorescence and 1 H NMR measurements in nonpolar solvents. The occurrence of unprecedented ultrafast photoinduced electron transfer from the porphyrin unit to the HAT unit in the CT π-complex was observed by femtosecond laser flash photolysis measurements. A highly linear aggregate composed of a planar porphyrin and an HAT derivative was observed by transmission electron microscopy (TEM) and atomic force microscopy (AFM).